An Analysis of the Effectiveness of Village Fund Management in Improving Community Welfare in Golat Village, Panumbangan Sub-district, Ciamis Regency - Lesmana, AI Indra; Sundarsih, Dedeh; Martianisari, Dewina; Mulyati, Sri; Andini, Dina (Equator Journal of Management and Entrepreneurship (EJME), 2025)
Golat Village is one of the villages located in the former Panumbangan District, situated on the northern slope of Mount Sawal, precisely in Panumbangan Sub-district, Ciamis Regency, West Java Province. This study aims to analyze the effectiveness of village fund management in improving the welfare of the community in Golat Village. The research employed a qualitative method. The researcher served as the primary instrument, utilizing data collection techniques including observation, interviews, documentation, and the operational measurement of effectiveness ratio to assess expenditure realization against targets. Findings from interviews and calculations of expenditure realization indicate that the effectiveness ratio of village fund management in Golat has increased from moderately effective (86%) to highly effective (98%). This is evident in the implementation of various programs. However, several obstacles were encountered during program implementation, such as limited human resource capacity, low community participation in planning and evaluation processes, and weather-related disruptions to physical development. Despite these challenges, village fund management has had a positive impact on community welfare, particularly in infrastructure and economic empowerment. To further enhance welfare, the village government should strengthen community empowerment programs and health education initiatives. Additionally, regular public education on climate change and adaptation strategies is necessary to mitigate the challenges of extreme weather.